Combination antiretroviral therapy improves recurrent primary biliary cholangitis following liver transplantation. (8th June 2021) - Lytvyak, Ellina; Niazi, Mina; Pai, Rohit; He, Daniel; Zhang, Guangzhi; Hübscher, Stefan G.; Mason, Andrew L.
Abstract: Recurrent primary biliary cholangitis (rPBC) is frequent following liver transplantation and associated with increased morbidity and mortality. It has been argued that rPBC behaves like an infectious disease because more potent immunosuppression with tacrolimus is associated with earlier and more severe recurrence. Prophylactic ursodeoxycholic acid is an established therapeutic option to prevent rPBC, whereas the role of second line therapies, such as obeticholic acid and bezafibrate in rPBC, remains largely unexplored. To address the hypothesis that a human betaretrovirus plays a role in the development of PBC, we have tested antiretroviral therapy in vitro and conducted randomised controlled trials showing improvements in hepatic biochemistry. Herein, we describe the utility of combination antiretroviral therapy to manage rPBC in two patients treated with open label tenofovir/emtricitabine‐based regimens in combination with either lopinavir or raltegravir. Both patients experienced sustained biochemical and histological improvement with treatment, but the antiretroviral therapy was associated with side effects.